Thai Morning Glory Price Forecasting Using Deep Learning - Kanokwan Waeodi; Laor Boongasame; Karanrat Thammarak (Applied Computational Intelligence and Soft Computing, 2025)
This study established advanced machine‐learning‐driven forecasting models to enhance the accuracy of price predictions for Thai morning glory, a widely consumed leafy green vegetable. The models were trained using historical price, weather, and rainfall data using time‐series forecasting methods, specifically LSTM and CNN. The findings indicate that stepwise feature selection minimizes prediction errors and improves MSE, RMSE, MAPE, and MAE. Preliminary experiments revealed that the LSTM model with feature selection outperformed the other models, particularly in feature selection. Employing standard hyperparameters of 100 epochs, 32 batches, and five windows, the model demonstrated superior performance with a lower MSE (0.0010), RMSE (0.0274), MAPE (3.7803), and MAE (0.0158) than the CNN model. Statistical hypothesis testing revealed significant variations between the LSTM and CNN models, with feature selection p ‐values below 0.05. These results indicate that LSTM with feature selection models optimized through refined hyperparameters leads to more accurate Thai morning glory price forecasting, providing valuable insights for stakeholders in their decision‐making processes. Additionally, this study can forecast prices for 5, 7, 14, and 21 days in advance based on different Window_len values, addressing various planning needs. The 5‐ and 7‐day forecasts support short‐term decision‐making, such as scheduling harvest cycles and weekly market planning, whereas the 14‐day forecast assists farmers in optimizing planting schedules and logistics. Furthermore, the 21‐day forecast is beneficial for medium‐term market planning, including negotiating forward contracts and adjusting distribution strategies to maximize profitability.
Keywords: Stock Market Forecasting Methods; Energy Load and Power Forecasting; Time Series Analysis and Forecasting